Izziv revščine v nekaterih mezopotamskih zakonikih in Svetem pismu - Skralovnik, Samo (Studia Historica Slovenica, 2017)
When comparing the (legal) concern for safety and protection of the poor in the (discussed) Mesopotamian codes and Bible, we find that the understanding of the issue of poverty is not exhausted on the basis of the results, obtained from comparative study of legal provisions. The comparison in background reveals a broader issue, of which a social challenge of poverty is only one of its many facets; it unveils the diversity of the concepts of perception of God and society on both sides.
Keywords: Biblija; Mezopotamija; revščina; Sveto pismo; svetopisemska zgodovina; zakoniki